Model ścieżki integracyjnej w benchmarkingu regionalnym - Strahl, Danuta (A model of integration path in regional benchmarking, 2005)
The article presents a proposal for a model of integration path applicable for regional benchmarking. The author suggests constructing a path to link the points determined on the basis of values of characteristics included in global and individual benchmark. The proposed procedure is illustrated with an example of an integration path for Poland during the country computerisation process with regard to the database for EU-member countries.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 11-17